Взаємодія форми правління та політичного режиму Української держави гетьмана П. П. Скоропадського - Мокін, Ігор Сергійович; Мокин, Игорь Сергеевич; Mokin, І. (My University, 2013)
In the article the correlation rule and state political regime of the Ukrainian state in 1918 and the general features of public-political regime of authoritarian democracy are defined. The fundamental priority of the monarchical form of government, especially in conditions of significant social changes is proved.
Мокін І. С.Взаємодія форми правління та політичного режиму Української держави гетьмана П. П. Скоропадського / І. С. Мокін / Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С. 468-477.
Keywords: політичний режим Української держави 1918 р.; форма правління в Україні 1918р.; загальні риси державно-політичного режиму авторитарної демократії; монархічна форма правління; історія України початку ХХ ст.; политический режим Украинского государства 1918 г.; форма правления в Украине 1918г.; общие черты государственно-политического режима авторитарной демократии; монархическая форма правления; история Украины начала ХХв.; political regime of the Ukrainian state in 1918; a form of government in Ukraine in 1918; general features of the state-political regime authoritarian democracy; monarchical form of government; History of Ukraine of the early twentieth century